1992
DOI: 10.1161/01.cir.86.4.1265
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial function and transmural blood flow during coronary venous retroperfusion in pigs.

Abstract: Considerable recovery of regional myocardial function with low regional capillary blood flows were observed during acute venous retroperfusion with high retroperfusion flows with arterial blood. These findings together with low levels of retrograde arterial outflow and visualization of retrograde capillary filling with a rich venous network provide evidence for possible oxygen delivery via the intramyocardial venous plexus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The left ventricular myocardium demonstrates transmural heterogeneity of strain distribution. It has been reported that, under normal circumstances, the subendocardial myocardium receives more blood flow and consumes more oxygen than the subepicardial one (20,28,35). Moreover, there is a transmural gradient of contractile function in the left ventricular wall, with greatest amount of thickening occurring in the subendocardial myocardium (6,25).…”
Section: Discussionmentioning
confidence: 99%
“…The left ventricular myocardium demonstrates transmural heterogeneity of strain distribution. It has been reported that, under normal circumstances, the subendocardial myocardium receives more blood flow and consumes more oxygen than the subepicardial one (20,28,35). Moreover, there is a transmural gradient of contractile function in the left ventricular wall, with greatest amount of thickening occurring in the subendocardial myocardium (6,25).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that blood entering the myocardium by patent channels is drained by the sinusoidal channel system [14, 15]. There is evidence that perfusion of the sinusoidal system can take over nutritive function [16, 17]and reestablish a sufficient myocardial blood supply. Transmyocardial channels created by laser remained longer patent than those produced by needle acupuncture [18]; however, in investigations with serial follow-up, it was documented that most of the transmyocardial laser channels occlude within weeks after their generation and that they are replaced by fibrous tissue [19, 20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…In 1948, Beck and colleagues (5) performed the coronary retroperfusion procedure in humans. The method was abandoned, however, because of the high mortality rate from the edema and hemorrhage in the postcapillary venules that resulted from the elevated pressure (6,8,12,26). To remedy these difficulties, we propose to avoid raising the pressure in the left anterior descending (LAD) vein from venous (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) to arterial values (100 -120 mmHg) in a single step.…”
mentioning
confidence: 99%